Diagnosis and management of rudimentary horn pregnancy rupture, misinterpreted as bicornuate uterus in the 14th week of pregnancy. Issue 2 (3rd December 2020) - Kozar, Nejc; Serdinšek, Tamara; Tašner, Tanja; Reljič, Milan; Gavrić Lovrec, Vida; Kovač, Vilma
Abstract: We present a 26‐year‐old primigravida with rudimentary horn pregnancy rupture at 14 weeks of pregnancy. Uterine anomaly was first diagnosed at the time of nuchal translucency scan and was presumed to be a bicornuate uterus with normal intrauterine pregnancy in the right horn. One day later, she was admitted to our department with abdominal pain, shortly leading to massive hemoperitoneum and hypovolemic shock. Uterine rupture was confirmed ultrasonically, followed by immediate laparotomy. Ruptured rudimentary horn with already expulsed pregnancy was encountered during surgery. Despite significant advances in ultrasonography, diagnosis of prerupture stage remains controversial. However, high mortality of the condition should ensure low threshold for surgical exploration.